Synergism of BCL-2 family inhibitors facilitates selective elimination of senescent cells - Rysanek, David; Vasicova, Pavla; Kolla, Jayaprakash Narayana; Sedlak, David; Andera, Ladislav; Bártek, Jiří; Hodny, Zdenek (Aging (Albany, NY. Online), 2022)
Accumulation of senescent cells in tissues with advancing age participates in the pathogenesis of several human age-associated diseases. Specific senescent secretome, the resistance of senescent cells to apoptotic stimuli, and lack of immune system response contribute to the accumulation of senescent cells and their adverse effects in tissues. Inhibition of antiapoptotic machinery, augmented in senescent cells, by BCL-2 protein family inhibitors represents a promising approach to eliminate senescent cells from tissues. This study aimed to explore synergistic and selective senolytic effects of anti-apoptotic BCL-2 family targeting compounds, particularly BH3 mimetics. Using human non-transformed cells RPE-1, BJ, and MRC-5 brought to ionizing radiation-, oncogene-, drug-induced and replicative senescence, we found synergy in combining MCL-1 selective inhibitors with other BH3 mimetics. In an attempt to uncover the mechanism of such synergy, we revealed that the surviving subpopulation of cells resistant to individually applied ABT-737/ABT-263, MIK665, ABT-199, and S63845 BCL-2 family inhibitors showed elevated MCL-1 compared to untreated control cells indicating the presence of a subset of cells expressing high MCL-1 levels and, therefore, resistant to BCL-2 inhibitors within the original population of senescent cells. Overall, we found that combining BCL-2 inhibitors can be beneficial for eliminating senescent cells, thereby enabling use of lower, potentially less toxic, doses of drugs compared to monotherapy, thereby overcoming the resistance of the subpopulation of senescent cells to monotherapy.
Keywords: Myeloid Cell Leukemia Sequence 1 Protein; protein MCL-1; apoptóza; lidé; stárnutí buněk; Proto-Oncogene Proteins c-bcl-2; protoonkogenní proteiny c-bcl-2; Cellular Senescence; Apoptosis; Humans